Growth and production of tomato fertilized with ash and castor cake and under varying water depths, cultivated in organic potponics - Daniela Pinto Gomes; Daniel Fonseca de Carvalho; Marinaldo Ferreira Pinto; David da Cunha Valença; Leonardo Oliveira Medici (Acta Scientiarum. Agronomy, 2017)
Two experiments were performed to evaluate the effect of ash (40, 80, and 120 g per plant), castor cake (140 and 280 g per plant) and water depth (135, 165, 191, and 213 mm) on the growth and production of organic tomato cultivated in pots in a greenhouse. The experimental design was randomized blocks, and the irrigation was managed using an automatic irrigation device. The following variables were evaluated: plant heights, numbers of leaves, bunches, flowers and fruits, total mass of fruits, mass of marketable fruits, mass of fruits with blossom-end rot, total diameter of fruits, and diameter of marketable fruits. Most of the growth variables showed gains with the application of 140 g of ash and 280 g of cake. The dose of 280 g of castor cake was responsible for the greatest mass of marketable fruits (1.78 kg per plant), regardless of the ash dose. The water deficit reduced values of most of the variables of growth and production. The irrigation depth of 213 mm was responsible for the greatest mass of marketable fruits (4.04 kg per plant). The highest water use efficiencies, 37.00 and 37.93 kg m-3, were observed at irrigation depths of 191 and 213 mm, respectively.